Association of Imaging-based Skeletal Muscle Metrics, Biochemical Markers, and MELD Score with Liver Transplant Complications and Survival: Insights from a Single-Center Cross-sectional Study - Dehghan, Pooneh; Ghiasi, Fatemeh; Langari, Seyedhassan; Rabbani, Amirhassan; Eghlimi, Hesameddin; Amiri, Mahmoud; Khoshroo, Javad (Novelty in Biomedicine, 2026)
Background: Identifying pre-transplant predictors of postoperative complications and survival following liver transplantation can improve patient outcomes and resource allocation. This study aimed to assess the predictive role of laboratory biomarkers and imaging-based parameters in post-transplant complications and patient survival. Materials and Methods: In this cross-sectional study, data from patients aged 17–75 years undergoing liver transplantation from deceased donors between October 2019 and December 2023 were retrospectively analyzed. Patients with malignancy, cardiovascular diseases, living donor transplants, or incomplete data were excluded. Preoperative clinical variables included demographics, MELD score, vascular features, biochemical laboratory parameters, and imaging-based muscle metrics (Skeletal Muscle Area, Skeletal Muscle Index, Skeletal Muscle Radiodensity Assessment, myosteatosis). Postoperative complications, survival status, and associated predictors were evaluated using appropriate statistical tests. Results: Of 79 patients (mean age 49.4 ± 12.2 years, 58.2% male), complications occurred in 39 (49.4%). Male sex (p=0.015) and lower SMRA (p=0.008) were significantly associated with postoperative complications. Patients who died had substantially higher MELD scores (23.3 ± 10.6) than survivors (17.3 ± 7.7; p=0.037). Portosystemic collaterals were significantly less frequent among patients with complications (23% vs. 50%, p=0.019). Routine biochemical laboratory parameters, SMA, SMI, myosteatosis, and vascular diameters were not significantly associated with outcomes. Kaplan-Meier survival analysis demonstrated an 85% survival rate at one year, with mortality primarily occurring within the first three months post-transplant. Conclusion: Pre-transplant MELD score tends to predict survival, whereas lower SMRA, male sex, and the absence of portosystemic collaterals may predict postoperative complications. Identifying these factors can enhance risk stratification and perioperative management in liver transplant recipients.